Trends and developments in oral health literacy: a scientometric research study (1991-2020) - Yue Sun; Chunying Li; Yan Zhao; Jing Sun (Nature Publishing Group, 2021)
Abstract Objective This study aimed to establish the current situation, intellectual base, hotspots, development trends, and frontiers of oral health literacy (OHL) from the literature. Methods We analyzed 1505 bibliographic records dated between January 1990 and December 2020 retrieved from the Web of Science Core Collection and the Scopus database. We used CiteSpace for word frequency analysis, co-occurrence analysis, co-citation analysis, clustering analysis, and burst analysis. Results The total number of publications increased year-on-year, with the majority of publications coming from the USA. Most studies focused on the relationship between (oral) health literacy and oral health, and the development of OHL instruments. The top 10 keywords by frequency were "health literacy", "oral health", "attitude to health", "dental caries", "adult", "children", "dental care", "knowledge", "questionnaire", and "adolescent". The keyword with the highest burst intensity was "dental health education". Conclusions OHL research is a thriving field. The field is focused on the development of an OHL instrument and health promotion practice. Strategic cooperation among countries, institutions, authors, hospitals, and communities will be important to encourage further OHL research and address oral health problems.